A highly symmetrical 10 transistor 2-read/write dual-port static random access memory bitcell design in 28 nm high-k/metal-gate planar bulk CMOS technology. (22nd March 2018) - Ishii, Yuichiro; Tanaka, Miki; Yabuuchi, Makoto; Sawada, Yohei; Tanaka, Shinji; Nii, Koji; Lu, Tien Yu; Huang, Chun Hsien; Chen, Shou Sian; Kuo, Yu Tse; Lung, Ching Cheng; Cheng, Osbert
Abstract: We propose a highly symmetrical 10 transistor (10T) 2-read/write (2RW) dual-port (DP) static random access memory (SRAM) bitcell in 28 nm high- k /metal-gate (HKMG) planar bulk CMOS. It replaces the conventional 8T 2RW DP SRAM bitcell without any area overhead. It significantly improves the robustness of process variations and an asymmetric issue between the true and bar bitline pairs. Measured data show that read current ( I read ) and read static noise margin (SNM) are respectively boosted by +20% and +15 mV by introducing the proposed bitcell with enlarged pull-down (PD) and pass-gate (PG) N-channel MOSs (NMOSs). The minimum operating voltage ( V min ) of the proposed 256 kbit 10T DP SRAM is 0.53 V in the TT process, 25 °C under the worst access condition with read/write disturbances, and improved by 90 mV (15%) compared with the conventional one.